Beauty Myth in Fat Chance, Charlie Vega: A Novel by Crystal Maldonado - Alya Della Syafira (Morphosis: Journal of Literature, 2024)
This study is entitled “ Beauty Myth in Fat Chance, Charlie Vega novel by Chrystal Maldonado”. This study used one of the literatures objects that was novel entitle Fat Chance, Charlie Vega. This novel described how the beauty concept was portrayed and how the main character rejected the beauty myth concept that judged women based on their appearance. This study used Naomi Wolf theory in her book The Beauty Myth which revealed how beauty myth oppressed women and encouraged women to not fall in beauty myth. The purposes of this study were to find out what the definition of beauty in the novel was and to find out how the character inside the novel rejected the beauty standard inside the novel. Furthermore, to interpret this study, the writer used qualitative data as the approach of the study which the date was taken from dialogues and narratives inside the novel. The results of this study shared the beauty concept oppressed women that women have to be slim to be called beautiful and another result showed how character rejected the beauty standard by doing self-love. In addition, the main character realized as time goes by that beauty was not always defined as slim. Self-love and fat-acceptance were the keys for women to feel beautiful. Keywords: beauty myth, fat-acceptance, qualitative.